(Machine translation from computerized Linguistic perspective: comparative study between (Google Translate and Microsoft Translator - Al Asmari, Ayed Mohammed (Arab Journal for Sciences and Research Publishing, 2018)
Machine translation is considered one the important subjects included in Linguistic Studies in general and computerized Linguistic in particular. Several Machine translation applications have emerged in the past years and the current research focuses on identifying the term of Machine translation using several texts and comparing the translation results of two famous Machine translation applications (Microsoft and Google translator). The results showed that Machine translation is one the modern terms emerged in Linguistic field, and many improvements has been conducted on Machine translation over the years in order to improve its results, hence, the findings indicated that human translation is more accurate and there are some defects in Machine translation and results of the current study approved theses defects by the translation model used in the study.
Keywords: Translation; machine translation; computational linguistics; human translation; applied model